2017
DOI: 10.1016/j.amepre.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Cigarettes Among U.S. Adults With Medical Comorbidities

Abstract: Introduction Electronic cigarette (e-cigarette) use is rising in the U.S. Smokers with comorbidities may increasingly use e-cigarettes if they believe e-cigarettes reduce smoking-related harm. This study examined e-cigarette use among adults with medical comorbidities. Methods In 2016, this study analyzed 68,136 U.S. adults in the 2014 and 2015 National Health Interview Survey. Prevalent e-cigarette use by medical comorbidities and adjusted odds of e-cigarette use were calculated. Results Among current cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 12 publications
1
49
3
Order By: Relevance
“…Electronic cigarette (e‐cigarette) use is prevalent among cigarette smokers in the US, including among those with medical comorbidities such as cancer . Smokers often report using e‐cigarettes to reduce or quit smoking or for health reasons, but reasons for use specifically among patients with cancer are unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic cigarette (e‐cigarette) use is prevalent among cigarette smokers in the US, including among those with medical comorbidities such as cancer . Smokers often report using e‐cigarettes to reduce or quit smoking or for health reasons, but reasons for use specifically among patients with cancer are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…13 To best counsel and assist cancer patients who smokers with smoking cessation, it is necessary to understand their use of other nicotine and tobacco products such as e-cigarettes. We aimed to describe, among smokers recently diagnosed with cancer: (1) prevalence and correlates of ecigarette use, (2) patterns of e-cigarette use, and (3) reasons for e-cigarette use.…”
mentioning
confidence: 99%
“…Similarly, dual users of e-cigarettes and combustible cigarettes in recent clinical trials were no more likely to quit combustible cigarettes at follow-up (Manzoli et al, 2016; Rigotti et al, 2017). Our findings are consistent with studies in the general population and within specific disease states such as acute coronary artery syndrome, serious mental illness and head and neck cancer (Prochaska and Grana, 2014; Busch et al, 2016; Manzoli et al, 2016; McQueen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the National Health Interview Survey suggests that cigarette smokers with medical comorbidities are more likely to use e-cigarettes (Kruse et al, 2017), yet few studies have examined the prevalence of e-cigarette use among inpatient smokers (Harrington et al, 2014; Baumann et al, 2015). In 1 study conducted in Birmingham, Alabama in 2012–2013, hospitalized smokers reported that they expected e-cigarettes to be less effective at relieving negative affect and satisfying nicotine cravings and that the taste would not be as pleasant as combustible cigarettes (Hendricks et al, 2015).…”
mentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) commonly results from years of smoking, but cessation can improve disease symptoms and reduce rate of lung function decline. Data suggest that former and current smokers with COPD are likely to use e‐cigarettes . A retrospective study conducted in four Italian hospitals compared patients with COPD reporting daily use of e‐cigarettes with age‐ and sex‐matched COPD patients reporting to be regular smokers .…”
Section: Patient Populationsmentioning
confidence: 99%